2014
DOI: 10.1021/ic5008507
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hydrothermal Crystal Growth, Structure, and Magnetic Properties of Ternary U(IV) Containing Fluorides: LiUF5, KU2F9, K7U6F31, RbUF5, RbU2F9, and RbU3F13

Abstract: Single crystals of several ternary alkali uranium fluorides, LiUF5, KU2F9, K7U6F31, RbUF5, RbU2F9, and RbU3F13, have been obtained in a mild hydrothermal process using UO2(CH3CO2)2(H2O)2 as the uranium source. Their crystal structures were determined by single crystal X-ray diffraction. The uranium in the starting reagent was successfully reduced from U(6+) to U(4+) in a dilute hydrofluoric acid environment, aided by the presence of a copper salt. All materials exhibit highly complex crystal structures that ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 61 publications
9
42
0
Order By: Relevance
“…Th, U) complex anions forming infinite layers or networks, respectively, are observed. [1,[3][4][5] The Np-F distances in [NpF 8 ] 4are observed in the range of 2.253(1) to 2.308(1) Å, whereas in [UF 8 ] 4the U-F distances at 150 K lie in between 2.257(1) and 2.335(1) Å. [6] An EXAFS study of (NH 4 ) 4 [NpF 8 ] at room temperature gave an average Np-F distance of 2.26(1) Å which nicely agrees with our results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Th, U) complex anions forming infinite layers or networks, respectively, are observed. [1,[3][4][5] The Np-F distances in [NpF 8 ] 4are observed in the range of 2.253(1) to 2.308(1) Å, whereas in [UF 8 ] 4the U-F distances at 150 K lie in between 2.257(1) and 2.335(1) Å. [6] An EXAFS study of (NH 4 ) 4 [NpF 8 ] at room temperature gave an average Np-F distance of 2.26(1) Å which nicely agrees with our results.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] In these ternary fluorides the anions usually form layer or network structures such as for example 2 ∞ [UF 3/3 F 4/2 F 2/1 ]in RbUF 5 or 3 ∞ [UF 8/2 F 1/1 ]in LiUF 5 . [3] In recent years single-crystal structure determinations of ternary fluoridometallates(IV) have mainly been carried out for Th and U compounds, whereas such studies and thus detailed structural parameters for compounds of the transuranium elements are lacking. [3][4][5][6][7] For the latter, usually only data obtained from powder diffraction studies have been reported, with the exception of a few single-crystal structure determinations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations